Negotiated shareholder value: The German version of an Anglo-American practice - Sigurt Vitols (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
In comparative political economy it has become commonplace to distinguish between two types of corporate governance systems. In shareholder systems, influence over company management is concentrated with institutional investors holding small percentages of companies' shares. In stakeholder systems, influence is shared between large shareholders, employees, the community, and suppliers and customers. This paper contributes to the literature addressing recent changes in the German variant of the stakeholder system by proposing a few new concepts. On the level of institutions, it is argued that the stakeholder system is not being replaced by a shareholder system in Germany. Rather, an augmented stakeholder system is emerging through the inclusion of institutional investors in the old stakeholder coalition of interests. On the level of practice, it is argued that negotiated shareholder value is being adopted in Germany. This German variant of shareholder value is distinct from Anglo-American practice because major changes implementing shareholder value must be negotiated within the augmented stakeholder coalition. As a result, performance incentives for employees tend to be less strong than is the case in the US and UK. – – In der vergleichenden politischen Ökonomie ist es Allgemeinplatz geworden, zwischen zwei Arten von Corporate-Governance-Systemen zu unterscheiden. In Shareholder-Systemen ist der Einfluss auf das Firmenmanagement bei institutionellen Investoren konzentriert, die kleine Anteile der Firmenaktien halten. In Stakeholder-Systemen ist dieser Einfluss geteilt zwischen Großaktionären, Beschäftigten, Gemeinde sowie Lieferanten und Kunden. Dieses Papier ist ein Beitrag zur Literatur über neue Veränderungen in der deutschen Variante des Stakeholder-Systems mit einigen neuen Konzeptvorschlägen. Auf der institutionellen Ebene wird behauptet, dass das Stakeholder-System in Deutschland nicht von einem Shareholder-System ersetzt werden wird. Eher wird eine erweiterte Stakeholder- Koalition durch die Einbeziehung der institutionellen Investoren in die bisherige Stakeholder-Koalition entstehen. Was die Praxis anbelangt, so wird behauptet, dass verhandelter Shareholder Value in Deutschland entsteht. Diese deutsche Variante des Shareholder Value unterscheidet sich von der anglo-amerikanischen Version dadurch, dass die Einführung von Shareholder Value-Maßnahmen innerhalb der erweiterten Stakeholder-Koalition verhandelt werden muss und die Leistungsanreize für Manager und Mitarbeiter weniger stark sind als in den USA und Großbritannien.
Keywords: G3; J5; P5; 330; Corporate governance; Shareholder Value; Varieties of Capitalism